9Å structure of the COPI coat reveals that the Arf1 GTPase occupies two contrasting molecular environments - Dodonova, Svetlana; Aderhold, Patrick; Kopp, Jürgen; Ganeva, Iva; Röhling, Simone; Sinning, Irmgard; Wieland, Felix T. (eLife, 2017)
A molecular model of the assembled COPI coat, determined by cryo-electron tomography of an in vitro reconstituted budding reaction, reveals details of interactions mediating coat assembly and shows the binding site of ArfGAP2.